ANALYSIS OF THE INFLUENCE OF MOTIVATION, FINANCIAL REWARD, INTERNSHIP EXPERIENCE, AND JOB MARKET CONSIDERANTION ON CAREER INTEREST IN ISLAMIC FINANCIAL INSTITUTIONS (STUDY ON SHARIA BANKING STUDENTS IN SEMARANG CITY). - Rosalia Putri Puspitasari; Muhammad Asrori; Nur Maziyah Ulya (Politeknik Negeri Semarang, 2023)
This study aims to analyze the significance of the effect of motivation, financial rewards, internship experience, and job market considerations on career interest at Islamic Financial Institutions on sharia banking students in Semarang City both simultaneously and partially. The population in this study were all students of the sharia banking study program in Semarang City. The sample used in the study 100 respondents who were selected using purposive sampling technique. The data used in this study are primary data obtained through the dissemination of questionnaires. The analysis model used in this study is a multiple linear regression analysis model, while the analysis technique uses a statistical test F, a coefficient of determination test (R2), and a statistical test t that is processed using the SPSS 25.00 program. The result of proving the hypothesis and discussion show that motivation, financial rewards, internship experience, and job market considerations simultaneously have a significant effect on career interest in Islamic Financial Institutions on sharia banking students in Semarang City. Partially, motivation has a positive and significant effect, financial reward has a negative but significant effect, internship experience has a positive and significant effect, and job market considerations has a positive but not significant effect on career interest in Islamic Financial Institutions on sharia banking students in Semarang City.Keywords: Career Interest, Motivation, Financial Reward, Internship Experience, and Job Market Consideration.